Management of Zakat in Indonesia | تنظيم الزكاة في إندونيسا - Khoirul Bahri Basyaruddin (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2019)
Zakat is a religious obligation, and one of the largest Islamic financial resources, organized since the second of hijriah.Zakat has been managed in Indonesia since before the independence era, but in colonial era zakat was declined, and began to stretch again after the independence of Indonesia.In Indonesia Zakat was initially managed by the Ministry of Religious Affairs of the Republic Indonesia, with issuing the Minister regulation in 1968, based on this and guided by 1945 Constituion which stated that Indonesia was founded on the One Godhead and freedom of whorship for every believer, than the government established Badan Amil Zakat Nasional (BAZNAS), and in 1999 the Government issued a special law on zakat management, wich later completed amended in 2011, pursuant to this special law government formed National Independent Zakat Authority.In terms of collecting an distributing Zakat managed by Badan Amil Zakat Nasional (BAZNAS) formed by the Government, and Lembaga Amil Zakat (LAZ) formed by the Islamic community based on applicable legal provisions, while the distribution carried out in two systems: distributing directly to mustahiq, and productive utilization.